Pharmacokinetics of Once‐Daily Extended‐Release Tacrolimus Tablets Versus Twice‐Daily Capsules in De Novo Liver Transplant. Issue 8 (22nd January 2019) - DuBay, Derek A.; Teperman, Lewis; Ueda, Kimi; Silverman, Andrew; Chapman, William; Alsina, Angel E.; Tyler, Carmelina; Stevens, Daniel R.
Abstract: The pharmacokinetics of once‐daily extended‐release tacrolimus tablets (LCPT) in de novo liver transplantation have not been previously reported. In this phase II, randomized, open‐label study, de novo liver transplant recipients were randomized to LCPT 0.07–0.13 mg/kg/day (taken once daily; n = 29) or twice‐daily immediate‐release tacrolimus capsules (IR‐Tac) at 0.10–0.15 mg/kg/day (divided twice daily; n = 29). Subsequent doses of both drugs were adjusted to maintain tacrolimus trough concentrations of 5 to 20 ng/mL through day 90, and 5–15 ng/mL thereafter. Twenty‐four‐hour pharmacokinetic profiles were obtained on days 1, 7, and 14, with trough concentration and efficacy/safety monitoring through year 1. Similar proportions of patients in both groups achieved therapeutic trough concentrations on days 7 and 14 (day 7: LCPT = 78%, IR‐Tac = 75%; day 14: LCPT = 86%, IR‐Tac = 91%) as well as similar systemic and peak exposure. There was a robust correlation between drug concentration at time 0 and area under the concentration‐time curve for both LCPT and IR‐Tac (respectively, day 7: r = 0.86 and 0.79; day 14: r = 0.93 and 0.86; P < .0001 for all). Dose adjustments during days 1 to 14 were frequent. Thirty‐five patients completed the extended‐use period. No significant differences in adverse events were seen between groups. Incidence of biopsy‐proven acute rejection (LCPT = 6 and IR‐Tac = 4) was similar on day 360. Between formulations, overall exposure was similar at 1 week after transplant with the characteristic delayed‐release pharmacokinetic profile of LCPT demonstrated in this novel population. These data support further investigation of the safety and efficacy of LCPT in de novo liver transplantation.